A Description of IVIG Use in Term Neonates with ABO Incompatibility - Daunov, Michael; Schlosser, Andrea; Malay, Sindhoosha; Adams, Jaclyn; Clark, Rachael; Ferrerosa, Lauren; Pateva, Irina (American Journal of Perinatology, 2024)
Objective This study aimed to determine if treatment with IVIG of neonates with ABO incompatibility (without Rh incompatibility) results in decreased number of packed red blood cell (pRBC) transfusions and phototherapy use.Study Design An Institutional Review Board (IRB)-approved, single-institution retrospective study was conducted. Neonates ≥38 weeks' gestational age born between January 1, 2007, and December 31, 2016, with ABO incompatibility were included. The comparison among groups was performed using chi-square and Fisher's exact tests for categorical variables; continuous variables were assessed by Kruskal–Wallis test.Results Six hundred and sixty-eight neonates with ABO incompatibility met inclusion criteria, 579 were included in the analyses. From these, 431 (74%) neonates had positive Direct Antiglobulin Test (DAT); 98 (17%) received IVIG and 352 (61%) received phototherapy. Thirty-six (6%) neonates received pRBC and 6 (1%) required exchange transfusions. Only 3 (0.5%) infants received pRBC transfusions postdischarge, by 3 months of age. Neonates requiring IVIG had lower initial hemoglobin (13.6 vs. 16.0 g/dL, p ≤ 0.0001) and higher bilirubin at start of phototherapy (9.1 vs. 8.1 mg/dL, p = 0.0064). From the 42 (7%) neonates who received simple and exchange transfusions, IVIG use was not associated with decreased use or number of transfusions (p = 0.5148 and 0.3333, respectively). Newborns with A+ and B+ blood types had comparable initial hemoglobin, DAT positivity, APGAR, and bilirubin. However, infants with B+ blood group were more likely (than A + ) to require phototherapy (p < 0.001), receive IVIG (p = 0.003), and need phototherapy for a longer duration (p = 0.001).Conclusion The results of this large retrospective study reveal that giving IVIG to neonates with ABO incompatibility was associated with increased simple or exchange transfusions. Newborns with B+ blood type required more phototherapy and IVIG. Further studies are needed to better stratify neonates who would benefit from IVIG use in order to optimize treatment strategies and avoid unnecessary risks and adverse events.Key Points
Keywords: hemolytic anemia; IVIG; ABO incompatibility